Management Accounting and Economic Analysis for Informed Decision Making - Kalidoss , Dr.D.; Shrikant , Dr. Anivilla (International Journal of Accounting and Economics Studies, 2025)
Using management accounting, nations all around the world have begun to increase their competitiveness.As a result, governments from different nations are taking action to establish regulations through different regulatory bodies for the good of the national economy and to give all operating industries an even playing field.It has been noted how several regulatory bodies have tried to reorient the sector toward a more open and transparent approach.The government makes decisions about different levies, export incentives, and excise taxes using a variety of methods, such as cost audits and the information gathered.In addition to helping the company gather data about different cost centers and processes, the management accountant is essential. The information aids in the company's strategy and decision-making by allowing it to compare itself to its counterparts.These statements might be submitted to management, shareholders, financial institutions, and regulators.However, financial data is also necessary for daily corporate decision-making and business monitoring.Management accounting is all about managing the financial data related to a company's operations. For a business to effectively respond and make informed decisions based on actual financial figures, having a reliable and relevant management accounting system and reports is crucial. This process helps managers analyse real financial results and understand the implications of their decisions. On the other hand, financial accounting focuses on creating financial statements and reports that are suitable for both internal use and external stakeholders.Internally, management accounting is most beneficial to the company.
Keywords: Financial Accounting; Transactions; Management